2023
DOI: 10.1002/ppp3.10408
|View full text |Cite
|
Sign up to set email alerts
|

A review of Madagascar's derived grasslands: Low palatability following anthropogenic fires may threaten food security

Grant S. Joseph,
Andrinajoro R. Rakotoarivelo,
Colleen L. Seymour

Abstract: Societal Impact StatementThe 26th United Nations Climate Change Conference emphasised the need to modify practices that negatively impact biodiversity and food security in the context of global change. Following Madagascar's drought‐induced famine, our systematic review supports the theory that grasslands of the Malagasy Central Highland that are subjected to human‐lit fires are anthropogenically derived. Furthermore, these overly frequent fires that characterise much of the Malagasy Central Highland grassland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 65 publications
(178 reference statements)
1
6
0
Order By: Relevance
“…If the first hypothesis were correct, extinct Malagasy hippos would have fed in open grasslands dominated by C 4 grasses (and have higher δ 13 C values), and browsing of C 3 woody vegetation in woodland and forested habitats would have been uncommon and atypical. Isotope data now clearly find that Malagasy hippos were mostly C 3 feeders, never predominant grazers, lived mostly in forest and browsed in moist and wooded habitats, even in regions that today are vast grasslands (Crowley et al, 2023), corroborating earlier studies that showed there never were pure C 4 grazing hippos (Crowley et al, 2021;Godfrey & Crowley, 2016;Hansford & Turvey, 2022;Joseph et al, 2024a). As Madagascar's hippos lived predominantly in forests and wetlands, their feeding strategy has been identified by various authors as similar to that of forest-limited African pygmy hippopotamus, Choeropsis liberiensis (Crowley et al, 2023;Hansford & Turvey, 2022), which does not form obligate C 4 grazing lawns .…”
Section: Introductionsupporting
confidence: 82%
See 4 more Smart Citations
“…If the first hypothesis were correct, extinct Malagasy hippos would have fed in open grasslands dominated by C 4 grasses (and have higher δ 13 C values), and browsing of C 3 woody vegetation in woodland and forested habitats would have been uncommon and atypical. Isotope data now clearly find that Malagasy hippos were mostly C 3 feeders, never predominant grazers, lived mostly in forest and browsed in moist and wooded habitats, even in regions that today are vast grasslands (Crowley et al, 2023), corroborating earlier studies that showed there never were pure C 4 grazing hippos (Crowley et al, 2021;Godfrey & Crowley, 2016;Hansford & Turvey, 2022;Joseph et al, 2024a). As Madagascar's hippos lived predominantly in forests and wetlands, their feeding strategy has been identified by various authors as similar to that of forest-limited African pygmy hippopotamus, Choeropsis liberiensis (Crowley et al, 2023;Hansford & Turvey, 2022), which does not form obligate C 4 grazing lawns .…”
Section: Introductionsupporting
confidence: 82%
“…Subfossil dietary confirmation of wooded habitat where today there is treeless grassland is further supported by the domination of the largest grasslands by pan-tropical, fire-adapted grasses and multidisciplinary evidence reveals that much of these grasslands are derived anthropogenic rangelands, degraded by human-lit fire (Joseph et al, 2024a). Malagasy grasslands are burned annually (Kull, 2003;Kull, 2004) and are grazed by introduced cattle, which are obligate C 4 grazers (Crowley et al, 2023;Joseph & Seymour, 2023a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations